Effectiveness of Green Infrastructure for Flood Mitigation in Semarang City - Rohan Kumar; Hana Tsegaye; Al Hamidy (Yayasan Adra Karima Hubbi, 2025)
Background. Flooding has become one of the most persistent environmental challenges in Semarang City, driven by rapid urbanization, land subsidence, and inadequate drainage systems. Conventional flood management approaches relying solely on grey infrastructure have proven insufficient to address the increasing frequency and intensity of flood events. Green infrastructure, including urban green spaces, bio-swales, retention ponds, and mangrove restoration, has emerged as a sustainable alternative that enhances natural water absorption and resilience against hydrological stress. Purpose. This study aims to evaluate the effectiveness of green infrastructure in mitigating floods in Semarang by assessing its hydrological, ecological, and socio-economic impacts. Method. A mixed-method approach was adopted, combining quantitative analysis of hydrological data with qualitative assessments from community surveys and expert interviews. Hydrological modeling using GIS and SWMM software was employed to simulate flood scenarios under different land-use configurations. Data on rainfall, surface runoff, and infiltration rates were collected from the Semarang Environmental and Public Works Agencies. Qualitative insights were gathered from local stakeholders to evaluate community perceptions of green infrastructure effectiveness and maintenance challenges. Results. The results indicate that green infrastructure interventions reduced peak flood levels by an average of 22–28%, improved runoff retention capacity, and enhanced groundwater recharge. Neighborhoods with integrated green spaces demonstrated greater resilience during heavy rainfall events compared to those relying solely on engineered drainage. Conclusion. The study concludes that the adoption of green infrastructure offers a cost-effective and ecologically sound strategy for urban flood mitigation in Semarang. Strengthening policy integration, maintenance systems, and community engagement is essential to sustain long-term resilience.